Automated three‐dimensional coded contrast imaging hysterosalpingo‐contrast sonography: feasibility in office tubal patency testing. (4th March 2013) - Exacoustos, C.; Di Giovanni, A.; Szabolcs, B.; Romeo, V.; Romanini, M. E.; Luciano, D.; Zupi, E.; Arduini, D.
ABSTRACT Objective To evaluate the feasibility of transvaginal hysterosalpingo‐contrast sonography (HyCoSy) with new automated three‐dimensional coded contrast imaging (3D‐CCI) software in the evaluation of tubal patency and visualization of tubal course. Methods Patients undergoing HyCoSy with automated 3D‐CCI software were evaluated prospectively. First, to evaluate the feasibility of 3D visualization of tubal course, we performed consecutive volume acquisitions while injecting SonoVue contrast agent. We then performed conventional two‐dimensional (2D) real‐time HyCoSy to confirm tubal patency status by detection of saline and air bubbles moving through the Fallopian tubes and around the ovaries. We also evaluated visualization with CCI of the contrast agent around the ovaries, side effects and pain during and after the procedure, by visual analog scale (VAS) (ranging from 0 to 10, with 0 corresponding to no pain and 10 corresponding to maximum pain). Results A total of 126 patients (252 tubes) underwent 3D‐CCI HyCoSy followed by 2D real‐time HyCoSy. According to the final 2D real‐time evaluation, bilateral tubal patency was observed in 111 patients, bilateral tubal occlusion in four patients and unilateral tubal patency in 11 patients. The concordance rate for tubal patency status between the first 3D volume acquisition and the final 2D real‐time evaluation was 84% and that between the second 3D volume acquisition and the final 2D real‐time evaluation was 97%. A pain score >5 on VAS was recorded in 58% of patients during the procedure, but a pain score ≤ 5 was recorded in 85.7% of patients immediately after the procedure. Conclusions HyCoSy with automated 3D‐CCI technology retains the advantages of conventional 2D HyCoSy while overcoming the disadvantages. 2D HyCoSy is highly observer‐dependent and is only accurate in the hands of experienced investigators; by obtaining a volume of the uterus and tubes, automated 3D volume acquisition permits visualization of the tubes in the coronal view and of the tubal course in 3D space, and should allow less experienced operators to evaluate tubal patency status relatively easily. Copyright © 2012 ISUOG. Published by John Wiley & Sons, Ltd.